The evaluation of performance in the European public e-health services sector by Generalized Estimating Equations. (February 2021) - Campanella, Francesco; Serino, Luana; Mustilli, Mario; Crisci, Anna; D'Ambra, Antonello
Abstract: Progressive attention to well-being and personal care is a salient aspect of modern living. In this sense, digital innovation can represent a fundamental strategic element to respond to challenges that arise today for the healthcare system. The purpose of this paper is to demonstrate: 1) the positive relationship between the use of ehealth information system and the level of consumer satisfaction; 2) the positive relationship between ehealth system and the organizational performance of health centers. The sample used for this empirical research is composed of 553 health care centers operating in Europe, during the years 2014-2017. Adopting the Generalized Estimating Equations for count data under Exchangeable working correlation structure, we show ehealth tools meet the needs and expectations of citizens, specifically, facilitating communication and accessing information and health resources, and at the same time they improve the quality of services with benefits in terms of organizational performance. Highlights: Consumers satisfactions. Ehealth. Generalized estimating equations. Organizational performance.